Proximal Migration of Pancreatic Duct Stent in Pancreas Divisum: Challenges in Retrieval and Review of the Literature - Subash Ghimire; Shri Jaikishan Ravi; Mohammad Yousef; Hafiz Khan (Case Reports in Gastrointestinal Medicine)
Pancreas divisum is the most common congenital malformation of the pancreas. Sometimes it is considered an etiology when patients present with recurrent episodes of pancreatitis. Endoscopic retrograde pancreatography (ERP) with selective cannulation of the minor papilla with sphincterotomy and stent placement are performed in these patients. Proximal migration of pancreatic stents in pancreas divisum is rare and challenging to manage. We describe a case of proximal migration of a pancreatic stent in a patient with pancreas divisum and perform a review of literature.